Between fascist purism and stylistic prescriptivism: the question of foreign words in Pietro Addeo’s Grammatica Forense - Dell’Anna, Maria Vittoria (Kwartalnik Neofilologiczny, 2026)
Piero Addeo, a lawyer and supporter of Fascism, wrote legal and linguistic works, including Grammatica forense (GF, 1935, 1938), which systematizes linguistic phenomena in public texts and critiques « incorrect » usage. This article examines Addeo’s treatment of foreign words and the relationship between Italian and other languages in institutional contexts, as seen in GF and minor works, ranging from linguistic xenophobia to stylistic precepts.